The effects of shift work on body weight change − a systematic review of longitudinal studies - Alwin van Drongelen; Cécile RL Boot; Suzanne Merkus; Tjabe Smid; Allard J van der Beek (Nordic Association of Occupational Safety and Health (NOROSH), 2011)
OBJECTIVE: This systematic review aims to summarize the available evidence to elucidate the effects of shift work, which includes night work, on body weight change. METHODS: A systematic search strategy using longitudinal studies was performed. Articles were included based on strict inclusion criteria; methodological quality was assessed by a standardized quality checklist. The results were summarized using a levels of evidence synthesis. RESULTS: The search strategy resulted in eight articles that met the inclusion criteria. Five of them were considered to be high- and three of them low-quality studies. Seven studies presented crude results for an association between shift work exposure and change in body weight: five high- and two low-quality studies. There was strong evidence for a crude relationship between shift work and body weight increase. Five studies presented weight-related outcomes adjusted for potentially relevant confounders (age, gender, bodyweight at baseline, and physical activity). Two studies found a significant difference between groups in the same direction. Consequently, the evidence for a confounders-adjusted relationship between shift work exposure and body weight was considered to be insufficient. CONCLUSIONS: Strong evidence for a crude association between shift work exposure and body weight increase was found. In order to further clarify the underlying mechanisms, more and better high quality studies about this subject are necessary.